REINTERPRETASI HADIS LARANGAN MELUKIS DAN LARANGAN PEREMPUAN BEPERGIAN TANPA MAHRAM ( Hermeneutika Fazlur Rahman) - Ghufron Hamzah (Jurnal Iqtisad, 2019)
Abstract The standardization process (textualization-normative) and dynamization (contextualization-historical) of Islamic teachings must indeed go together so that the formula which states that Islam is "appropriate for every time and place" (ṣāliḥ li kulli zamān wa makān) can show the flexibility and elasticity of Islam, not strict and rigid orthodoxy. One such effort is the study in this paper that seeks to reinterpret the hadith editorial prohibition on painting and the prohibition of women traveling without mahram by using Fazlur Rahman's hermeneutical approach, so that contextual understanding will be obtained by adhering to the moral ideal of the hadith message. Keywords: Hadith Prohibition of painting and traveling without mahram, Hermenutika Fazlur Rahman Abstrak Proses pembakuan (tekstualisasi-normatif) dan dinamisasi (kontekstualisasi-historis) ajaran Islam memang harus berjalan bersama-sama agar formula yang menyatakan Islam itu “sesuai untuk setiap waktu dan tempat” (ṣāliḥ li kulli zamān wa makān) dapat menunjukkan fleksibilitas dan elastisitas Islam, bukan ortodoksi yang ketat dan kaku. Salah satu upaya tersebut adalah kajian dalam tulisan ini yang berusaha melakukan reinterpretasi atas redaksi hadis larangan melukis dan larangan perempuan bepergian tanpa mahram dengan menggunakan pendekatan hermeneutika Fazlur Rahman, sehingga akan didapatkan pemahaman yang kontekstual dengan berpegang pada ideal moral pesan hadis tersebut. Kata Kunci: Hadis Larangan melukis dan bepergian tanpa mahram, Hermenutika Fazlur Rahman